Pernambuco "feminina", mulher fêmea, sim! The woman in the Alto do Moura mazurka: cultures, experiences and music (Orfeu, 2020)
The subordination of women is a universal, ancient phenomenon and is the first form of oppression of humanity (Ana COSTA; Cecília SARDENBERG, 2008). Studies that address the relationship between women and music, or music and gender, still need to emerge more, although there has been a growing trend in the field in recent years. This paper aims to present the presence of women (as creators, performers,muses,mestras)in MazurcaPéQuente do Alto do Moura, pointing to the importance of the contexts in which music is inserted, as well as of works that talk about women in the musical field. Interviews, observations and informal conversations were carried out with the members of the mazurka. Most of the data was collected for the “Inventário do Ofício dos Artesãos e Artesãs do Barro do Alto do Moura – Caruaru-PE”.
Keywords: Alto do Moura; Mazurka; Woman; Music